2017
DOI: 10.1097/mib.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Most Appropriate Delivery Mode in Women with Inflammatory Bowel Disease

Abstract: New long-term data from well-designed studies are needed, but our review suggests that systematic CS in patients suffering from IBD should probably be limited to women at risk of perineal tears and obstetric injuries, with an active PCD, or with ileal pouch anal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 32 publications
1
49
0
6
Order By: Relevance
“…Uncomplicated vaginal delivery does not worsen the course of IBD, even in the case of perianal injury. However, such patients should be considered on an individual basis, and active disease in the perianal area remains a contraindication for vaginal delivery because of potential adverse events that could affect continence . In the present study, there were 22 cesarean deliveries for women with IBD in the first period, but none in the second period owing to the stricter assessment criteria.…”
Section: Discussionmentioning
confidence: 70%
“…Uncomplicated vaginal delivery does not worsen the course of IBD, even in the case of perianal injury. However, such patients should be considered on an individual basis, and active disease in the perianal area remains a contraindication for vaginal delivery because of potential adverse events that could affect continence . In the present study, there were 22 cesarean deliveries for women with IBD in the first period, but none in the second period owing to the stricter assessment criteria.…”
Section: Discussionmentioning
confidence: 70%
“…Fecal urgency is defined as having difficulty deferring a sudden or compelling desire to defecate. 5,14,[16][17][18][19][20] The role of planned CS in order to prevent OASIS, AI, and the potential impact of delivery on women's future health remains unclear 1,7,21 A Cochrane Review concluded that planned CS showed no benefit in the prevention of AI in postpartum women. 2,12,13 Furthermore, other studies have shown that AI, in particular, may have a devastating impact on women's social, emotional, and physical activity as well as their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 AI is associated with increasing age, obesity, pregnancy, instrumental VD, and obstetric anal sphincter injury (OASIS). 5,14,[16][17][18][19][20] The role of planned CS in order to prevent OASIS, AI, and the potential impact of delivery on women's future health remains unclear 1,7,21 A Cochrane Review concluded that planned CS showed no benefit in the prevention of AI in postpartum women. 7 The aim of this study was to explore whether women who only had delivered vaginally were at greater risk of developing AI than women who had undergone only cesarean sections or women who had never experienced childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review reached the conclusion that uncomplicated vaginal delivery only moderately influenced pouch function, with no significant difference in overall continence or stool frequency. Nevertheless, function was significantly worsened in a complicated delivery, perhaps still justifying an elective caesarean in these patients [847]. Regarding patients who have an ileorectal anastomosis, there is clearly intact rectal function and patients may not be so 'borderline incontinent'.…”
Section: Mode Of Delivery After Surgery For Ulcerative Colitismentioning
confidence: 98%